1995
DOI: 10.1161/01.atv.15.11.1987
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoproteins Inhibit Cytokine-Induced Expression of Endothelial Cell Adhesion Molecules

Abstract: While an elevated plasma concentration of HDLs is protective against the development of atherosclerosis and ensuing coronary heart disease (CHD), the mechanism of this protection is unknown. One early cellular event in atherogenesis is the adhesion of mononuclear leukocytes to the endothelium. This event is mediated principally by vascular cell adhesion molecule-1 (VCAM-1) but also involves other molecules, such as intercellular adhesion molecule-1 (ICAM-1) and E-selectin. We have investigated the effect of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
445
3
15

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 710 publications
(477 citation statements)
references
References 39 publications
14
445
3
15
Order By: Relevance
“…HDL has been demonstrated in vitro to decrease neutrophil degranulation and superoxide production, 32 inhibit LDL oxidation, 33 protect endothelial cells against the effects of oxidized LDL, 34 and prevent the cytokine-induced upregulation of adhesion molecules on endothelial cells, 35 effects that have not been demonstrated to be specifically due to the apoA-I component of the HDL particle. HDL contains a variety of proteins in addition to apoA-I that have been shown to be antiatherogenic in vivo, including apoE, 19,20 apoA-IV, 21,22 LCAT, 23 CETP, 24 and paraoxonase.…”
Section: Discussionmentioning
confidence: 99%
“…HDL has been demonstrated in vitro to decrease neutrophil degranulation and superoxide production, 32 inhibit LDL oxidation, 33 protect endothelial cells against the effects of oxidized LDL, 34 and prevent the cytokine-induced upregulation of adhesion molecules on endothelial cells, 35 effects that have not been demonstrated to be specifically due to the apoA-I component of the HDL particle. HDL contains a variety of proteins in addition to apoA-I that have been shown to be antiatherogenic in vivo, including apoE, 19,20 apoA-IV, 21,22 LCAT, 23 CETP, 24 and paraoxonase.…”
Section: Discussionmentioning
confidence: 99%
“…28,43 ApoE-deficient mice lacking the macrophage scavenger receptor A had a 58% decrease in atherosclerosis. 44 The vascular wall is implicated in studies using cultured endothelial and/or smooth muscle cells, which suggests that differences in lipoprotein retention, 45 adhesion molecule expression, 46 and subendothelial matrix components 47,48 would be likely to affect foam cell lesion formation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study, which show that patients with increased levels of triglycerides and low HDL cholesterol have increased levels of sCAMs, are consistent with previous in vitro studies showing that oxidized fatty acids increase endothelial expression of CAMs in response to cytokines, whereas high levels of HDL inhibit the endothelial expression of CAMs in response to cytokines. 9 Omacor contains 3.3 IU/g of vitamin E, which may have prevented the enhanced oxidation of fatty acids seen in some studies with fish oils. 23 These data suggest that increased expression of CAMs may be a mechanism by which high triglyceride/low HDL promotes atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that low HDL and oxidized fatty acids increase the endothelial expression of CAMs in response to cytokines. [6][7][8][9] Assessment of the relationship between elevated triglycerides/low HDL and the expression of CAMs in humans has been hampered by the difficulty of quantitative assessment of CAM expression in vivo.…”
mentioning
confidence: 99%